Comparison of resiliency, optimism and social selfefficacy in delinquent and normal adolescents / Fahime Rajabi and Sedigheh Salmanpour - Rajabi, Fahime; Salmanpour, Sedigheh (Penerbit UiTM, 2019)
The presentstudy aimed to examine and compare resilience, optimism, and self-efficacy in delinquent and normal adolescents in Fars Province, Iran. The statistical population comprised 100 delinquent adolescents in Shiraz Juvenile DetentionCentre and 100 normal adolescents. Research hypotheses were investigated in this descriptive-analytical study using Scheier and Carver's Life Orientation Test, the Connor-Davidson Resilience Scale, and Sherer's Self-Efficacy Scale and statistical analysis was conducted using independent samples t-test. Results showed that there was a significant difference between two groups of adolescents in terms of the optimism, resilience and self-efficacy. The optimism in adolescents had a significant impact on the mental health and behaviour of them and plays an important role in the personal and social life of individual. Furthermore, the resilience and self-efficacy have crucial roles in the life of adolescents. Having any of these traits and enhancing and improving them play important roles in the life of adolescents.